Gaia Net: Toward Robust Spectroscopic Parameters of Stars of all Evolutionary Stages - Dylan Huson; Indiana Cowan; Logan Sizemore; Marina Kounkel; Brian Hutchinson (The Astrophysical Journal)
We present a new processing of XP spectra for 220 million stars released in Gaia DR3. The new data model is capable of handling objects with T _eff between 2000 and 50,000 K and with $log\,g$ between 0 and 10, including objects of multitude of masses and evolutionary stages. This includes for the first time ever robust processing of spectroscopic parameters for pre-main-sequence stars, with $log\,g$ sensitivity toward their age. Through this analysis we examine the distribution of young low-mass stars with ages of up to 20 Myr in the solar neighborhood, and we identify a new massive (>1000 stars) population, Ophion, which is found east of Sco–Cen. This population appears to be fully disrupted, with negligible kinematic coherence. Nonetheless, due its young age it appears to still persist as a spatial overdensity. Through improved determination of ages of the nearby stars, it may be possible to better recover the star-forming history of the solar neighborhood outside of the moving groups.